SMA-origami coupling: online configuration switches and stability property modulation - Hai Zhou; Hongbin Fang; Zuolin Liu; Jian Xu (International Journal of Smart and Nano Materials, 2024)
ABSTRACTActive folding is a crucial requirement for practical applications of multi-stable origami structures. However, research on integrating active materials with origami structures to enable quick configuration switching and modulation of stability properties is still in its early stages. To advance the state-of-the-art, we designed a coupled structure comprising a stacked Miura-origami (SMO) structure and two Shape Memory Alloy (SMA) actuators. One actuator is used for extruding the SMO structure while the other is used for retracting, thereby realizing bidirectional reversible active folding of the coupled structure. Modeling the potential energy of the coupled structure shows that it can be switched between monostable and bistable by heating the SMA actuators. The above findings are also confirmed by experiments conducted on a delicate SMO-SMA coupled structure prototype. The activation of different actuators induces rapid configuration switching of the coupled structure, and the stability profile is qualitatively adjusted by designing the current loading profile to achieve steady-state temperature fluctuations. Overall, this study provides a new approach to coupling origami structures with smart materials for active folding and presents a novel method to regulate the stability property of origami structures, thus promoting their practical applications.